Effects of aqueous plant extracts on the phagocytic capability and intracellular killing of Staphyococcus Aureus by Murine peritoneal macrophages in vitro - Mahmood, A.A.; Khiarul Anwar, A.; Ansary, A.; Sidik, K.; Salmah, I.; Suzainur, K.A.R. (Faculty of Medicine, University of Malaya, 2001)
Nine local plant species were picked randomly and their aqueous extracts been screened to know their effects on the phagocytic capability and intracellular killing Staphylococcus aureus bacteria by mouse peritoneal macrophages. Macrophage cultures were incubated with different concentration of each plant extracts for 1 hour. Among these aqueous extracts, Ageratum conyzoides and Malastoma melabathricum inhibited the phagocytic capability and intracellular killing of staphylococcis aureus compared with controls. Elicited (activated) cells have more phagocytic capability and intracellular killing than the resident (normal) macrophages. There were no differences in the viability of cells between treated cells betweem treated cells (withextracts) and contgrols (without extracts)